Transcriptome Analysis of Tetraploid and Octoploid Common Reed (Phragmites australis) - Wang, Cui; Wang, Tong; Yin, Meiqi; Eller, Franziska; Liu, Lele; Brix, Hans; Guo, Weihua (Frontiers in Plant Science, 2021)
Polyploidization in plants is thought to have occurred as coping mechanism with environmental stresses. Polyploidization-driven adaptation is often achieved through interplay of gene networks involved in differentially expressed genes, which triggers the plant to evolve special phenotypic traits for survival. Phragmites australis is a cosmopolitan species with highly variable phenotypic traits and high adaptation capacity to various habitats. The species’ ploidy level varies from 3x to 12x, thus it is an ideal organism to investigate the molecular evolution of polyploidy and gene regulation mediated by different numbers of chromosome copies. In this study, we used high-throughput RNAseq data as a tool, to analyze the gene expression profiles in tetraploid and octoploid P. australis. The estimated divergence time between tetraploid and octoploid P. australis was dated to the border between Pliocene and Pleistocene. This study identified 439 up- and 956 down-regulated transcripts in tetraploids compared to octoploids. Gene ontology and pathway analysis revealed that tetraploids tended to express genes responsible for reproduction and seed germination to complete the reproduction cycle early, and expressed genes related to defense against UV-B light and fungi, whereas octoploids expressed mainly genes related to thermotolerance. Most differentially expressed genes were enriched in chaperones, folding catalysts and protein processing in endoplasmic reticulum pathways. Multiple biased isoform usage of the same gene was detected in differentially expressed genes, and the ones upregulated in octoploids were related to reduced DNA methylation. Our study provides new insights into the role of polyploidization on environmental responses and potential stress tolerance in grass species.